Web-based amateur critical reviews in comparison to traditional television counterparts - Kelley, Jonathon (University of Wisconsin--Whitewater, 2015)
Since 1907 film criticism has been a part of the mass media. In the 1970s film criticism made a leap from the pages of the local newspaper to television programming in the form of Sneak Previews hosted by Gene Siskel and Roger Ebert. Reaching a peak in ratings by 1992, the show was regularly being viewed by millions. In recent years as programming has moved from the television to the internet as a result of the digital revolution, a new breed of reporters have attempted to fill the shoes that critics like Siskel & Ebert left behind. This study analyzed one specific web based film criticism program, Half in the Bag, and compared the content recently presented by that program to 1992 episodes of Siskel and Ebert. Data was gathered in from both sources for the total length spent reviewing the film, the focus on opinion, the use of film terminology and the overall likelihood of critics to recommend a film. The goal of the study was to ultimately determine if content provided by modern day web based film critics is truly comparable to the works completed by Gene Siskel and Roger Ebert in the early 1990s. Research indicated that while appearing like their traditional counterparts, in many ways they were not comparable. Thus, while the overall trend seems to be leading to a convergence of the internet and television, and a movement of programing from the television to the web, web based film review programs like Half in the Bag are not presenting the same content that previous television reviewers did, but rather a new form of film review that focuses on analysis and a specific niche audience.
This file was last viewed in Microsoft Edge PDF viewer.
Keywords: Film criticism; Mass media--Technological innovations